2010
DOI: 10.1016/j.juro.2010.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Silver or Nitrofurazone Impregnation of Urinary Catheters Has a Minimal Effect on Uropathogen Adherence

Abstract: Purpose-Bacterial adherence to the urinary catheter is an early step in biofilm formation and the pathogenesis of catheter associated urinary tract infection. We studied in vitro the effect of silver or nitrofurazone impregnation of urinary catheters on uropathogen ability to adhere to urinary catheters.Materials and Methods-We studied commercially available nitrofurazone-silicone, silicone only, silver-silicone-hydrogel, silicone-hydrogel, silver-latex-hydrogel and latex-hydrogel catheters. Catheters were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 26 publications
3
88
1
2
Order By: Relevance
“…concluded that impregnation of catheters with silver or nitrofurazone did not significantly affect bacterial adherence in comparison to control catheters 19 . Whilst the evidence generally confirms the affirmative role of local antimicrobial delivery, it is appreciated that the delivery of the antimicrobial agent from such coatings is not fully understood nor optimised, particularly within the respiratory environment in which the volume of fluid for drug elution is limited.…”
Section: Introductionmentioning
confidence: 93%
“…concluded that impregnation of catheters with silver or nitrofurazone did not significantly affect bacterial adherence in comparison to control catheters 19 . Whilst the evidence generally confirms the affirmative role of local antimicrobial delivery, it is appreciated that the delivery of the antimicrobial agent from such coatings is not fully understood nor optimised, particularly within the respiratory environment in which the volume of fluid for drug elution is limited.…”
Section: Introductionmentioning
confidence: 93%
“…Again, Ag 7 NO 11 had a low MBC against planktonic populations, prevented biofilm formation, and eradicated established biofilms at lower concentrations than those of AgNO 3 and CuSO 4 . Certainly, Ag has been explored as a strategy to control infection by uropathogens (72) as well as to combat and control antibioticresistant pathogens, including MRSA (67,(73)(74)(75)(76). The results from this study demonstrated variable sensitivities of the planktonic and biofilm populations to CuSO 4 , AgNO 3 , and Ag 7 NO 11 .…”
Section: Discussionmentioning
confidence: 75%
“…One review (Schumm & Lam, 2008) concluded that silver alloy catheters did decrease the occurrence of asymptomatic bacteriuria in patients undergoing both short term and long term catheterisation, although this decrease was less pronounced in those patients catheterised for over a week. Desai et al (2010) found that nitrofurazoneimpregnated catheters had only a minimal preventative effect in the earlier stages of E.coli and E.faecalis biofilm development (< 5 days) and that silver impregnation had a negligible effect. The incorporation of a silver releasing device between the drainage tube and catheter was found to provide an antibacterial barrier that could protect against bacterial colonisation for periods of at least 10 days in the bag and 8 days for the tubes and catheters (Stickler et al, 1994).…”
Section: Biofilms On Indwelling Medical Devicesmentioning
confidence: 93%
“…The adhesion of microorganisms to urinary catheters is particularly problematic. Catheter associated urinary tract infections (CAUTI) are the most common hospital acquired infection (Desai et al, 2010). Urinary catheters are tubular, latex or silicon devices inserted into the bladder via the urethra for a variety of purposes including collection of urine during surgery, measuring urine output, prevention of urine retention and control of urinary incontinence (Schumm & Lam, 2008).…”
Section: Biofilms On Indwelling Medical Devicesmentioning
confidence: 99%